2022
DOI: 10.1063/5.0079555
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol transmission in passenger car cabins: Effects of ventilation configuration and driving speed

Abstract: Identifying the potential routes of airborne transmission during transportation is of critical importance to limit the spread of the SARS-CoV-2 virus. Here, we numerically solve the Reynolds-averaged Navier–Stokes equations along with the transport equation for a passive scalar in order to study aerosol transmission inside the passenger cabin of an automobile. Extending the previous work on this topic, we explore several driving scenarios including the effects of having the windows fully open, half-open, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Natural ventilation is a low-cost, economical, and energy-saving alternative in land public transportation. It can effectively reduce the infection risk, which has been verified in real cases [67 , 68 , 70] , experiments [35 , 39 , 66] , and modeling [38 , 48 , 50 , [53] , [54] , [55] , 72 , 81 , 82] . When the vehicle is driving, the external airflow generates a pressure distribution over the vehicle - the areas near the front are lower-than-atmospheric pressures, while the areas toward the middle and rear of the vehicle are neutral or higher-than-atmospheric pressures ( Fig.…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…Natural ventilation is a low-cost, economical, and energy-saving alternative in land public transportation. It can effectively reduce the infection risk, which has been verified in real cases [67 , 68 , 70] , experiments [35 , 39 , 66] , and modeling [38 , 48 , 50 , [53] , [54] , [55] , 72 , 81 , 82] . When the vehicle is driving, the external airflow generates a pressure distribution over the vehicle - the areas near the front are lower-than-atmospheric pressures, while the areas toward the middle and rear of the vehicle are neutral or higher-than-atmospheric pressures ( Fig.…”
Section: Resultsmentioning
confidence: 71%
“…The same applied to the minibus and taxis, only opening the front windows provided the most ventilation compared to only opening the middle windows or the rear windows [84] . Moreover, inlet ports at the frontal and sunroof could also effectively carry fresh air into the vehicle [48 , 54 , 81 , 85] . Two studies revealed that when the infector was near ventilation openings, especially the windows in the row in front of the infector, could effectively remove his exhaled droplets and thereby reduce the infection risk of other passengers [50 , 55] Meanwhile, droplets generated by the front-seated person were easier to be discharged by opening windows than that generated by rear-seated passengers [38 , 53] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations